Female behavior affects offspring survival in roe deer (Capreolus capreolus) - Tooke, Daniel (SLU/Dept. of Ecology, 2018)
The concept of individual behavior and personality is a convoluted concept within ecology. In essence, how individual variations in behavior may affect an individual’s success in survival and reproduction as compared to other individuals who behave differently. This study aimed to investigate how individual variation in primarily behavior, but also physiological differences, of roe deer (Capreolus capreolus) does affected fawn survival during the first two months of life. The study was based upon individuals captured in two areas of central Sweden. A number of variables attributed to behavior and physiology were gathered through trapping of roe deer, using baited box traps. Uncorrelated variables were progressively analyzed through a series of logistic regression models. Three variables were related to fawn survival based upon these models; the average spatial distance between mother and fawn, the mother’s behavior during handling, and, to a lesser degree, release. The negative relationship between fawn survival and distance between mother and fawn is mainly tied to the success rate of protecting her fawn from predators with the doe’s presence. Mother behavior during capture and release was concluded to be tied to levels of vigilance and boldness in the mother; individual behavior which seems to affect fawn survival.